1997
DOI: 10.1143/ptp.97.49
|View full text |Cite
|
Sign up to set email alerts
|

Strong Gravitational Lensing and Velocity Function as Tools to Probe Cosmological Parameters: Current Constraints and Future Predictions

Abstract: Constraints on cosmological models from strong gravitational lensing statistics are investigated. We pay particular attention to the role of the velocity function in the calculation of the lensing probability. The velocity function derived from the observed galaxy luminosity function, which is used in most previous work, is unable to predict the large separation lensing events. In this paper, we also use the Press-Schechter theory to construct a velocity function theoretically. Model predictions are compared w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 70 publications
1
73
0
Order By: Relevance
“…with Δ vir (z) being the critical overdensity for virialisation at redshift z (Kitayama & Suto 1996;Nakamura & Suto 1997;Henry 2000). We take the fitting formula from Weinberg & Kamionkowski (2003) …”
Section: Appendix A: the Halo Modelmentioning
confidence: 99%
“…with Δ vir (z) being the critical overdensity for virialisation at redshift z (Kitayama & Suto 1996;Nakamura & Suto 1997;Henry 2000). We take the fitting formula from Weinberg & Kamionkowski (2003) …”
Section: Appendix A: the Halo Modelmentioning
confidence: 99%
“…This means that shocks in the inner regions of clusters may not be fully reproduced. However, those shocks in high-density regions are expected to be weak with low 8 The relation between r 200 and r vir is rather complicated and depends on cosmological parameters (e.g., Nakamura & Suto 1997;Bryan & Norman 1998;Eke et al 1998 Mach numbers of M s 2-3 (e.g., Vazza et al 2011), so their contribution to the production of CRs would not be significant (see the discussion in Section 2.3). Since this paper focuses on relatively strong, CR-producing shocks in the outskirts, having an uniform resolution throughout the entire simulation volume should be actually an advantage.…”
Section: Cluster Samplementioning
confidence: 99%
“…They also revealed that the concentration parameter of the NFW profile, namely the ratio of the virial radius to the scale radius, c vir = r vir /r s , is much higher than predicted by cosmological N -body simulations (e.g., Bullock et al 2001;Neto et al 2007). We note that the virial radius, r vir , within which the mean interior density is ∆ vir ≃ 110 (Nakamura & Suto 1997) times the critical mass density, ρ cr (z), at a cluster redshift is given by…”
Section: A Joint X-ray and Lensing Analysismentioning
confidence: 99%